Influence of carbohydrate malabsorption syndrome on the clinical course of rotavirus infection in children at an early age - Vorobiova, N.; Usachova, O. V.; Воробьева, Н. В.; Усачева, Е. В.; Воробйова, Наталія Володимирівна; Усачова, Олена Віталіївна (My University, 2021)
The aim of the work - to determine the pathogenetic role of carbohydrate malabsorption syndrome in severity and duration of rotavirus infection symptoms in early aged children. The study included 60 breastfed children aged 1-24 months with rotavirus infection. The severity and duration of the main symptoms of rotavirus gastroenteritis were analyzed depending on the dynamic changes in laboratory parameters of carbohydrate malabsorption syndrome: the total amount of reducing carbohydrates in feces, lactose and glucose in feces, which were determined on II-III, V, VII and X days of the disease. To determine the total amount of reducing sugars in the coprofiltrates, the Benedict’s test was used, the lactose in the feces was determined using the Malfatti’s test, and the glucose was determined by the Glucophane test systems (Erba Lachema). It was found that the syndrome of carbohydrate malabsorption had the maximum pathogenetic effect on the severity of rotavirus diarrhea after the fifth day of the disease mainly due to lactase deficiency. Starting from the seventh day of rotavirus infection, with an increase in the level of carbohydrates in the feces by 0,5%, the frequency of liquid stools increases by 1 time per day. The prognostic sign of long-term diarrheal syndrome (≥9 days) is the total level of reducing sugars in the feces ≥1% on the fifth day of illness. If the result of the Benedict’s test increases by 0,4% in this term, the duration of diarrhea increases by 1 day. When the level of carbohydrates in the stool ≥ 0,75% on the tenth day of the disease the risk of residual effects on discharge from the hospital (such as unstable stools 2-3 times a day, meteorism and flatulence) increases. Обследовано 60 детей в возрасте 1-24 месяцев, на грудном вскармливании с ротавирусной инфекцией. Проведен анализ тяжести и длительности основных симптомов болезни в зависимости от динамических изменений лабораторных показателей синдрома мальабсорбции углеводов: общего количества восстанавливающих сахаров, лактозы и глюкозы в кале, которые определяли на II, III, V, VII и X дни болезни. Для определения общего количества углеводов в копрофильтратах использовали пробу Бенедикта, лактозы – пробу Мальфатти, глюкозы – тест-системы «Глюкофан» производства Erba Lachema (Чехия). Установлено, что синдром мальабсорбции углеводов оказывает максимальное патогенетическое влияние на тяжесть ротавирусной диареи после пятых суток болезни и реализуется в большей мере за счет лактазной недостаточности. Начиная с седьмого дня при увеличении уровня углеводов в кале на 0,5%, частота жидких испражнений возрастает на 1 раз в сутки. Прогностическим признаком длительного диарейного синдрома (≥9 дней) при ротавирусной инфекции является общий уровень олигосахаридов в кале ≥1% на пятый день болезни. При увеличении показателя пробы Бенедикта на 0,4% длительность диареи увеличивается на 1 день. При уровне углеводов в кале >0,75% на десятые сутки болезни увеличивается риск возникновения остаточных явлений при выписке из стационара, таких как неустойчивый стул 2-3 раза в сутки, метеоризм и флатуленция.
Влияние синдрома мальабсорбции углеводов на клиническое течение ротавирусной инфекции у детей раннего возраста
Keywords: rotavirus infection; carbohydrate malabsorption syndrome; lactase deficiency; early age children; Benedict’s test